2020
DOI: 10.1016/j.sdentj.2019.10.004
|View full text |Cite
|
Sign up to set email alerts
|

Effect of smoking on patient-reported postoperative complications following minor oral surgical procedures

Abstract: Objective This study evaluated the effect of smoking on patient-reported postoperative complications after minor oral surgical procedures by comparing the post-extraction symptoms between smokers and nonsmokers. Materials and methods Patients undergoing minor oral surgical procedures were recruited and followed up prospectively on the first, second, seventh, and twenty-first days after simple dental extractions. Results A total of 85 patients… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(12 citation statements)
references
References 25 publications
0
12
0
Order By: Relevance
“…However, when comparing the results of HA and A-PRF groups regarding pain reduction, a statistically significant decrease on the third postoperative day is only in favor of the A-PRF group; this result may be explained by the fact that A-PRF aids in the acceleration of healing and angiogenesis and minimizes the danger of inflammation in the region of application [ 18 20 ]. Since the severity of the postoperative pain resulting from minor oral surgeries usually fades in days following the surgery [ 21 ], it might explain the disappearance of A-PRF preference over hyaluronic acid on the seventh postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…However, when comparing the results of HA and A-PRF groups regarding pain reduction, a statistically significant decrease on the third postoperative day is only in favor of the A-PRF group; this result may be explained by the fact that A-PRF aids in the acceleration of healing and angiogenesis and minimizes the danger of inflammation in the region of application [ 18 20 ]. Since the severity of the postoperative pain resulting from minor oral surgeries usually fades in days following the surgery [ 21 ], it might explain the disappearance of A-PRF preference over hyaluronic acid on the seventh postoperative day.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking has been associated with multiple post-operative complications after dental extractions; a frequently reported complication in smokers is post-operative pain; one clinical study, in particular, reported a significant difference when they compared smokers with non-smokers; however, they reported no differences relatively to the number of cigarettes smoked [ 39 ]. Another commonly reported complication is alveolar osteitis.…”
Section: Discussionmentioning
confidence: 99%
“…According to a recent systematic review [ 40 ], this complication is highly common in smokers who undergo both traumatic and atraumatic dental extractions, with a prevalence rate of 13.2% compared with non-smokers (3.8%). In addition to the above-mentioned complications, smoking has been linked to many other consequences, including trismus, swelling, and infection [ 39 ]. Therefore, present ongoing efforts are aimed to find treatments or applications that can overcome the occurrence of smoking-related biological deterioration.…”
Section: Discussionmentioning
confidence: 99%
“…Smoking may disrupt the formation of blood clot in the socket and hinder the normal healing process of the socket, that eventually delay the healing of the socket. 20 Moreover, smoking also has an effect on the levels of pain as smokers tend to experience greater levels of postoperative extraction pain as compared to the non-smokers. 21 Different studies have been carried to evaluate its effectiveness in controlling pain, trismus and swelling.…”
Section: Discussionmentioning
confidence: 99%